Mixture (Codemixing) of Languages Including Minangkabau, Indonesian and Chinese in Padang City - Aditiawarman, Mac; Kartika, Diana (International Journal of Psychosocial Rehabilitation, 2020)
Mixture (Codemixing) of Languages Including Minang, Indonesian And Chinese In Padang City. The language is known as Padang Tiong Hoa (Tiong Pa). The language has been used for a long time. The mixture of Padang Tiong Hoa language happened through three ways: they are the mixing of Indonesian language, Chinese, and Minangkabau language elements. The three language elements combine together and build a new Minangkabau language variant that is called Tiong Pa language. This research applies the distributional method. The aim of this research is to describe the rules of the vowel and consonant diphthong changing in the mixture of Tiong Pa language. The result of this research can be contributed to the linguistics field. The result of this research indicates that: (1) the final deletion of vowel /-a/; (2) the medial deletion of vowel /-a-/; (3) the final deletion of /-ah/; (4) the final deletion of consonant /-h/; (5) the medial deletion of vowel /-i-/; (6) the medial deletion of vowel /-e-/; (7) the final changing of vowel /-o/ to /-a/; (8) the medial changing of vowel /-a-/ to /-∂-/; (9) the final changing of diphthong /-ai/ to /-e/; (10) the medial changing of diphthong /-ia-/(/-ai-/) to vowel /-e-/; (11) the medial changing of /-i-/ to /-e-/; (12) the final changing of diphthong /-ia/ to vowel /-e/; (13) the final changing of diphthong /-au/ to vowel /-o/; (14) the medial changing of vowel /-u-/ to /-o-/; (15) the medial changing of diphthong /-ua-/ to vowel /- o-/; and (16) the medial changing of vowel /-a-/ to /-o-/.